Dinâmica de ocupação, vulnerabilidades e cenários para a bacia hidrográfica do rio Vermelho, Goiás - Vieira, Pedro Alves (2013)
The historical process of occupation and land use in the Cerrado biome has been accompanied by different rates and conversion levels. Recent surveys indicate that about 50% of the original Cerrado cover has been already converted to large-scale agriculture. In Goiás, this process started with the mining activity, in the early XVIII century. However, the first governmental development policies start only in the early 40’s, under the govern of Getulio Vargas, and only in the 60’s, with the goals set by President Juscelino Kubitschek, became trully effective. In face of the historical land use dynamics, eventually over highly vulnerable areas, the Cerrado suffered a significant loss in environmental quality. An example in this direction is the medium Araguaia basin, which presents a stock of sandy sediments of about 200 million tons, in part fed by the upper Rio Vermelho basin, where sediment loss reaches 2 million tons a year. Within this context, this study, based on field, census, and orbital data (from different acquisition periods and with different resolutions), integrated and analyzed via GIS and scenario modelling techniques, pursued the identification, for the total area of the Rio Vermelho basin (nearly 11,000 km2), of different classes of natural vulnerability (relying on the mapping of entropy levels, as well as on tectonic and physiografic patterns), relatively to the occupation process, in four distinct periods (1976, 1987, 2002 e 2008). Approximately 65% of the basin area has been converted, which caused a severe environmental impact, affecting ~40% of the permanent protected areas (mainly around springs, lakes, and rivers), as well as ~9% of highly vulnerable areas. The occupation analysis for two distinct periods, i.e. 1976 (start) and 1987 (end), suggests that soil fertility and occupation fronts already established are the dominant factors controlling the basin fate, with new occupations being directed and concentrated along the main road network.